2004
DOI: 10.1160/th04-02-0124
|View full text |Cite
|
Sign up to set email alerts
|

Platelet deposition on stainless steel, spiral, and braided polylactide stents

Abstract: Platelets play a key role in (sub)acute thrombotic occlusion after stenting. We examined the possible differences between biodegradable polylactide (PLA) and stainless steel (SS) stents in platelet attachment and morphology after whole blood perfusion. PLA stents of different configurations (spiral/braided) and polycaprolactone-polylactide (PCL-PLA)-coatings, or SS stents were implanted into a PVC tube (Ø 3.2 mm), with or without precoating of the tube with type-I collagen. PPACK (30 microM)-anticoagulated blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…79 Hietala et al analyzed platelet deposition on stainless steel and PLLA stents, with the latter showing increased platelet adhesion. 13 However, when coating the PLLA stent with a PLCL layer, platelet attachment was effectively reduced. This behavior was also reported by Rudolph et al regarding the thrombogenetic potential of different polymers following a platelet activation test.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…79 Hietala et al analyzed platelet deposition on stainless steel and PLLA stents, with the latter showing increased platelet adhesion. 13 However, when coating the PLLA stent with a PLCL layer, platelet attachment was effectively reduced. This behavior was also reported by Rudolph et al regarding the thrombogenetic potential of different polymers following a platelet activation test.…”
Section: Resultsmentioning
confidence: 99%
“…9–11 Other strategies involve the use of polydopamine (PDA) and polyethylenimine (PEI) as intermediates to incorporate an anti-platelet and anti-thrombotic drug 12 or an anticoagulant drug such as heparin. 13,14 Similarly, Meng et al 15 applied a layer-by-layer strategy to coat 316L stainless steel coronary stents with chitosan and heparin to accelerate re-endothelialization after coronary stent deployment. Alternatively, titanium oxide films have been reported as a suitable coating to improve endothelialization.…”
Section: Introductionmentioning
confidence: 99%
“…The MSS surface was coated with sulfonated CH using dopamine and PEG as anchors and was reported to limit platelet activation and clot formation, as well as calcium deposition [207]. The PCL-PLA-HEP coating enhanced hemocompatibility and reduced platelet deposition [208]. In a study, a small number of platelets adhered to alginic acid-immobilized MSS substrates [209].…”
Section: Improvement Of Hemocompatibilitymentioning
confidence: 99%
“…To investigate the biocompatibility of biodegradable polymers, cultured monocytes differentiated into functional macrophages were incubated with various polymers including poly-L-lactide, polycaprolactone, or poly-D,L-lactide-co-glycolide for up to 5 days and showed that biodegradable polymers were associated with macrophage adhesion, NADPH oxidase-induced generation of ROS, and excess apoptosis [ 89 ]. Furthermore, Hietala et al [ 90 ] examined the possible differences between biodegradable polylactide (PLA) and stainless steel (SS) stents in platelet attachment and morphology after whole blood perfusion. Results revealed that more platelets deposited on PLA stents than on SS stents under all study conditions ( P < 0.03), while among all biodegradable stents, the braided PLA stent coated with PCL-PLA-heparin accumulated the fewest platelets ( P < 0.02), indicating that materials, design, and coating techniques of biodegradable stents must be further developed.…”
Section: Biodegradable Polymer Stents and Drug-eluting Absorbable mentioning
confidence: 99%